Introduction - Izarra, Laura P.Z.; Mutran, Munira H. (ABEI Journal, 2002)
The publication of this issue of the ABEI Journal coincides with the hosting of IASIL 2002, the International Conference for the Study of Irish Literatures, by the University of São Paulo. Our expectations are high because this will be the first time that what must be considered as the heart of Irish Studies has travelled to South America.